2008
DOI: 10.1200/jco.2008.17.6511
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase IX Expression in Clear Cell Renal Cell Carcinomas Negatively Correlates With the Proportion of the Granular Cell Component

Abstract: 9. Bleumer I, Knuth A, Oosterwijk E, et al: A phase II trial of chimeric monoclonal antibody G250 for advanced renal cell carcinoma patients. Br J Cancer 90:985-990, 2004 10. Bleumer I, Oosterwijk E, Oosterwijk-Wakka JC, et al: A clinical trial with chimeric monoclonal antibody WX-G250 and low dose interleukin-2 pulsing scheme for advanced renal cell carcinoma. J Urol 175:57-62, 2006 11. Steffens MG, Boerman OC, de Mulder PH, et al: Phase I radioimmunotherapy of metastatic renal cell carcinoma with 131 I-label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Interestingly, Skapa et al. 27 noted recently that the amount and intensity of reactivity of CAIX in CRCC was related to the proportion of cells with granular cytoplasm, which may explain the lower percentage of CRCC that expressed CAIX in our study. In addition, the reactivity of CAIX in ChRCC was primarily weak in nature.…”
Section: Discussioncontrasting
confidence: 58%
“…Interestingly, Skapa et al. 27 noted recently that the amount and intensity of reactivity of CAIX in CRCC was related to the proportion of cells with granular cytoplasm, which may explain the lower percentage of CRCC that expressed CAIX in our study. In addition, the reactivity of CAIX in ChRCC was primarily weak in nature.…”
Section: Discussioncontrasting
confidence: 58%
“…Although not statistically significant the data presented here highlight the need for future studies to be conducted on the angiogenesis pathway and to identify new targets for providing better information for treatment selection and prognostic modelling. The results from our data follow the literature and show CA9 and VEGF (19,20) as possible targets for further work.…”
Section: Discussionsupporting
confidence: 87%
“…It is also important to note that several studies when conducting IHC staining on prepared slides (in an assay similar to those described in our methods) used a semiquantitative scoring system of absent/weak/strong. Maybe the further elucidation of a five tiered scoring system has sub-divided the relatively small sample size and proved to be a limitation to the data analysis and that of a more simple approach (one reflected in Leibovich et al and Skapa et al) would yield more interesting results (12,20).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the independence of various factors must be assessed as there may be links between several predictive factors-for example, CAIX expression is inversely correlated with numbers of granular cells. 23 Such issues along with validation of other markers are also being assessed in the "SELECT" study 24 and initial results were reported at ASCO 2010. 25 It is interesting to note that these results 25 do not confirm to the selection criteria proposed by Upton et al 14 or the value of CAIX to select patients for HD IL2.…”
Section: Discussionmentioning
confidence: 99%